2014
DOI: 10.1002/app.40487
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic liquid crystalline copolyesters with low Tm and high Tg: Synthesis, characterization, and properties

Abstract: In this study, a series of aromatic copolyesters P‐BPAx with lower melting temperature and higher glass transition temperature derived from hydroxybenzoic acid (HBA), 6‐hydroxy‐2‐naphthoic acid (HNA), bisphenol A (BPA) and terephthalic acid (TA) were synthesized via melt polymerization. The copolyesters were characterized by FTIR, solid state 13C NMR, DSC, TGA, polarized optical microscopy, X‐ray diffraction, and rheometry measurements. With addition of BPA, the resulting copolyester's melting temperature decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 42 publications
3
17
0
Order By: Relevance
“…This increase in T m caused by the HBA monomer of the rigid rod-type can be attributed to the ease of molecular packing. [21][22][23][24] The isotropic temperature (T i ) showed the same trend as the T m (Table 3). A liquid crystalline phase was not observed for TLCPs with 0-2 mol HBA because of the bent structure of DHN and the exible alkoxy side group of DTA, as was observed for the T m .…”
Section: Resultssupporting
confidence: 52%
“…This increase in T m caused by the HBA monomer of the rigid rod-type can be attributed to the ease of molecular packing. [21][22][23][24] The isotropic temperature (T i ) showed the same trend as the T m (Table 3). A liquid crystalline phase was not observed for TLCPs with 0-2 mol HBA because of the bent structure of DHN and the exible alkoxy side group of DTA, as was observed for the T m .…”
Section: Resultssupporting
confidence: 52%
“…Liquid crystallinity, which occurs between T m and T i , can be observed using an optical polarizing microscope [34,35]. Figure 5 shows the liquid crystallinity observed for polymers in the TLCP-I and TLCP-II series at various temperatures.…”
Section: Liquid Crystalline Mesophasementioning
confidence: 99%
“…According to the Bragg equation, the interplanar space corresponding to each peak can be obtained. Among them, the average intermolecular space (2θ = 20.0°) reflecting the rodlike liquid crystalline mesogens is 4.4 Å, and the interplanar spaces of 2θ = 27.9° and 2θ = 43.1° belong to the (211) crystallographic plane of the HBA homopolymer (pHBA). , Its average intermolecular spaces are 3.2 and 2.1 Å, respectively, implying the presence of highly thermally stable pHBA (nano)­crystallites . Through observing photomicrographs, it is found that cured RLCP still manifests the typical nematic liquid crystalline texture (Figure B); hence, the curing process does not influence its liquid crystallinity because of the outstanding thermal stability of the all-aromatic liquid crystalline main chain and steady liquid crystallinity of RLCP over a broad temperature range (Figure ).…”
Section: Resultsmentioning
confidence: 99%